Performance evaluation of a ZigBee-based medical sensor network - Fernández-López, Helena (2009)
Low power consumption and small footprint make 802.15.4/ZigBee based devices well suited for personal healthcare applications, representing a promising alternative to patient monitoring under important scenarios such as emergency, postop, continuous care, and chronic diseases. However, their use in a healthcare facility to monitor several mobile patients poses several difficulties, mainly because this protocol was primarily designed to operate in low data rate scenarios. This paper presents simulation results used to evaluate important quality of service (QoS) markers and, ultimately, estimate the maximum number of sensors that could integrate a wireless vital signs monitoring system. Results show that the system is able to carry the signals from 30 ECG sensors with delivery ratio higher than 99% in the considered scenario, provided that an adequate number of retransmissions are allowed.